COLLAPSING CARDIOVASCULAR AND RESPIRATORY PHYSIOLOGY: INCREASING TRENDS OF WHEAT PILLS (ALUMINUM PHOSPHIDE) POISONING IN RURAL NAWABSHAH, INTENSIVE CARE UNIT BASED OBSERVATIONS - Muhammad Naeem; Muhammad Saleh Khaskheli; Rafia Tabassusm; Ashique Ali Arain; Aziz Ahmed Solangi; Abdul Ghafoor (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Study Objective: This study was aimed at determining the frequency and percentage of wheat pill poisoning with its clinical presentation and outcomes in our tertiary care ICU. Study Design and settings: It was an observational study conducted in ICU of the People’s University of medical and health sciences Nawabshah from June 2023 to December 2023. Material & Methods: Patients reported as the suicidal and accidental poisoning with wheat pills were admitted in the ICU and the treatment was provided according to emergency protocols. The required data was collected using the research proforma. Collected data was interpreted and results were generated using statistical package of social sciences 22. Result: We admitted 20 patients as the victims of wheat pill (aluminum phosphide) poisoning out of which 10 (50%) were males and 10(50%) were females with a male female ratio of 1:1 for involvement. There were 7(35%) cases which belonged to 30 years or below age group while 13(65%) cases belonged to the age group above 30 years. Only one patient survived while 19 patients couldn’t be saved with a mortality rate of 95%. Conclusion: Suicidal Wheat pill poisoning is becoming a common practice in the rural area of this region being an easily available and cheaper option whereas the accidental poisoning with this agent is very rare in this area.